2017
DOI: 10.1002/joc.5260
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic classification in 21st century CMIP5 predictions over the Eastern Mediterranean with focus on cyclones

Abstract: The semi‐objective synoptic classification was used to investigate future changes in the occurrence of EM synoptic types, with an emphasis on Cyprus Lows (CL). A significant reduction in CL occurrence is found towards the end of the 21st century. The reductions in CLs are accompanied by an increase in the frequencies of Red Sea Troughs and Highs in winter. The predicted changes in the occurrence of various synoptic types will lead to a more accurate forecast of climatic hazards. The eight CMIP5 models average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 41 publications
4
62
0
Order By: Relevance
“…Due to the absence of 12UTC data at the 1,000‐hPa level in CMIP5 models, we use U and V wind components and temperature from the 850‐hPa level, as well as sea level pressure (SLP). The compatibility between the 1,000 and the 850‐hPa levels, and that of the 12UTC with daily classifications was examined by Hochman et al (, c) and Berkovic (), respectively, and was shown to fit well. Nevertheless, the ability of the two downscaling methods used, that is, the modified algorithm for the synoptic classification (the “weather regimes”) and the “analogues” to downscale observed seasonal precipitation is evaluated here for both the NCEP/NCAR reanalysis and the CMIP5 models.…”
Section: Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…Due to the absence of 12UTC data at the 1,000‐hPa level in CMIP5 models, we use U and V wind components and temperature from the 850‐hPa level, as well as sea level pressure (SLP). The compatibility between the 1,000 and the 850‐hPa levels, and that of the 12UTC with daily classifications was examined by Hochman et al (, c) and Berkovic (), respectively, and was shown to fit well. Nevertheless, the ability of the two downscaling methods used, that is, the modified algorithm for the synoptic classification (the “weather regimes”) and the “analogues” to downscale observed seasonal precipitation is evaluated here for both the NCEP/NCAR reanalysis and the CMIP5 models.…”
Section: Methodssupporting
confidence: 90%
“…However, it should be stressed that precipitation is highly parametrized in the GCMs, therefore, this should not influence our findings. We suggest that the overestimation in the frequency of wet days and the underestimation of the daily precipitation may be mostly related to the general overestimation of the frequency of Cyprus Lows over the eastern Mediterranean (Hochman et al, ) and the location and depth of these cyclones in the GCMs. These features exert a strong control on daily precipitation over Israel (Saaroni et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the 1‐mm threshold for number of wet days and number of CWD is reasonable coinciding with Hochman et al . (), which found that about 20% of the days are classified as precipitation producing systems (Goldreich, ).…”
Section: Resultsmentioning
confidence: 99%